Design and Build IoT-Based Lavender Plant Smart Pots: Rancang Bangun Pot Pintar Tanaman Lavender Berbasis IoT - Satrio, Adi Indra; Saputra, Dwi Hadidjadja Rasjid (Universitas Muhammadiyah Sidoarjo, 2021)
This research started from plant observation, preparation, design of component and circuit specifications, assembly, work steps, and evaluation. The results of the study will prove the tool works or not, if the soil moisture sensor detects the soil moisture is reduced by 50%, then the sensor will respond and send a signal to the microcontroller to activate the relay so that the pump will turn on automatically. The monitoring system on the device can be accessed via a smartphone, the signal is sent by the smartphone and then captured by the microcontroller, then processed and the output can be an image of the monitored plant. This tool is also equipped with a water reservoir that can also be monitored from a smartphone. If the water in the reservoir reaches 30% of the capacity of the reservoir, the Water Level sensor will send a signal to the microcontroller and warn that the water level is very low, then send an order to the owner to immediately fill the reservoir. At night this tool is also equipped with an LDR sensor if the light intensity is less then the LED will light up.